„Die Toten der Zukunft sind / Die nicht wachbleiben / In diesem Traum / Im Heiligen Theater des Jetzt“. Messianische Zeitlichkeit im Theater Werner Fritschs. - Eke, Norbert (Zukünftigkeit im zeitgenössischen Drama und Theater. Literatur- und theaterwissenschaftliche Studien.)

(Prä-)Modernität? Das Ringen um Zeit und Zeitgenossenschaft in der Literatur der Vormärz- und der Revolutionsepoche. - Eke, Norbert (Die Modernität von 1848/49. Ambivalente Aufbrüche und neue Zugänge zur Revolution.)

Erkundungen im destrukturierten Süden. Marlene Streeruwitz‘ literarisches Maskenspiel Die Reise einer jungen Anarchistin in Griechenland (2014). - Eke, Norbert (Deutsche Griechenland-Diskurse und Griechisch-Deutscher Kulturtransfer.)

Unverfügbarkeit – Latenz – Widmung. Das Heilige (in) der Kultur. - Eke, Norbert (Das Heilige (in) der Kultur. Unverfügbarkeit – Latenz – Widmung.)

Epochenzugehörigkeit und Werkentwicklung. - Eke, Norbert (Gotthelf-Handbuch. Leben – Werk – Wirkung.)

Was im Gedicht geschieht. Jan Wagner, Paderborn Wintersemester 2023/24: Die 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2. 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller.)

Unschärfen – Ambiguitäten – Mehrdeutigkeiten. Eine ( Jan Wagners) poetologische ‚Klarstellung‘ lyrischer Praxis. - Eke, Norbert (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2. 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller.)

Alltagskultur im Vormärz. Vorbemerkung. - Eke, Norbert (Alltagskultur im Vormärz (= FVF Jahrbuch 2024).)

Erste Begegnung. - Eke, Norbert (Literatur in Westfalen. Beiträge zur Forschung 20.)

IBB: Fast Burrows-Wheeler Transform Construction for Length-Diverse DNA Data - Adler, Enno; Böttcher, Stefan; Hartel, Rita; Steininger, Cedric Alexander (23rd International Symposium on Experimental Algorithms)

Der Abgrund in deutscher und baltischer Kultur / The Abyss in German and Baltic Culture. Hg. von Marko Pajević und Jaanus Sooväli.

Julia Menzel: Holocaust, Zeit und Erzählung. Traumatische Zeiterfahrung in H. G. Adlers Roman Eine Reise.

Izabela Rakar: Verbreiterte Breitenwirkung. Thomas Kling, seine Vorgänger, Zeitgenossen und Nachfolger

Jakub Gortat: Remembering National Socialism in Austrian Post-war Film (1945-1955).

Don't Touch the Power Line - A Proof-of-Concept for Aligned LLM-Based Assistance Systems to Support the Maintenance in the Electricity Distribution System - Kaltenpoth, Sascha; Müller, Oliver (ACM SIGEnergy Energy Informatics Review)
As a possible solution to the demographic change and the resulting knowledge loss due to retirements in the Energy sector, this study aimed to develop a generic pipeline to implement and evaluate proof-of-concepts (PoCs) for LLM-based assistance systems in new domains. Our pipeline contains an LLM-based data generation strategy based on documents, a retrieval-augmented generation (RAG) architecture utilizing prompting techniques on existing German LLMs, and an LLM-based automatic evaluation strategy. We leverage our pipeline to evaluate five LLMs using data from a German DSO. We found that the Llama3 and the Mistral model are appropriately aligned for the task. We plan to pilot the RAG architecture in the DSO's infrastructure for future research and continuously research improvements using the generated human demonstrations.

A Step Towards Cognitive Automation: Integrating LLM Agents with Process Rules - Kaltenpoth, Sascha Benjamin; Skolik, Alexander Marcus; Müller, Oliver; Beverungen, Daniel (Lecture Notes in Computer Science)

Hermann, Michael, „Der Wandel von Statistik zu Maschinellem Lernen“, SieB. Siegener Beiträge zur Geschichte und Philosophie der Mathematik 17 (2023), 145–179. - Peckhaus, Volker (zbMATH Open, Zbl. 07925543)

EU-Projekt CREXDATA: Erkenntnisse und Handlungsempfehlungen zum Einsatz KI-generierter Lageinformationen für die Lagebewertung und Maßnahmenplanung in Extremwetterlagen - Pottebaum, Jens; Gräßler, Iris; Ebel, Marcel; Özcan, Deniz; Döhner, Niklas; Pratzler-Wanczura, Sylvia; Derin, Enes; Krüger, Oliver; Kruijff-Korbayova, Ivana; Stampa, Merlin

Visualization Task Taxonomy to Understand the Fuzzing Internals - Kummita, Sriteja; Miao, Miao; Bodden, Eric; Wei, Shiyi (ACM Transactions on Software Engineering and Methodology)
Greybox fuzzing is used extensively in research and practice. There are umpteen publications that improve greybox fuzzing. However, to what extent do these improvements affect the internal components or internals of a given fuzzer is not yet understood as the improvements are mostly evaluated using code coverage and bug finding capability. Such an evaluation is insufficient to understand the effect of improvements on the fuzzer internals. Some of the literature visualizes the outcomes of fuzzing to enhance the understanding. However, they only focus on high-level information and no previous research on visualization has been dedicated to understanding fuzzing internals. To close this gap, we propose the first step towards development of a fuzzing-specific visualization framework: a taxonomy of visualization analysis tasks that fuzzing experts desire to help them understand the fuzzing internals. Our approach involves conducting interviews with fuzzing experts and using qualitative data analysis to systematically extract the task taxonomy from the interview data. We also evaluate the support of existing fuzzing visualization tools through the lens of our taxonomy. In our study, we have conducted 33 interviews with fuzzing practitioners and extracted a taxonomy of 120 visualization analysis tasks. Our evaluation shows that the existing fuzzing visualization tools only provide aids to support 10 of them.

The Need for Diffraction in STEM -fields: An Ethical Feminist Consideration of the Concept of Genderscripting - Grewe, Felix (Feminist Encounters Special Issue on Peripheral Visions of Alternative Futures: Feminist Techno-imaginaries)